Corporate governance and corporate social responsibility disclosure in Indonesia: The moderating effect of foreign ownership - Pratama, Ikbar (2023)
The trend of research on corporate social responsibility disclosure (CSRD) shows a growing concern on the information content and its trustworthiness, creating apprehension about the whole practice in corporate social reporting. The objective of this study is to examine the extent of CSRD in Indonesian public listed companies (PLC), the relationship of CSRD with corporate governance attributes, and the moderating effect of foreign ownership on the relationship between corporate governance attributes and CSRD using the legitimacy theory, agency theory, and stakeholder theory. The measurement for CSRD is based on quantity (number of pages) and quality (index). Further, the measurement of CSRD quality (index) is based on 25 items according to the practices in Indonesia. Data collection was based on the environment and social items disclosed in annual reports and the sample of the study consists of 353 companies listed in the Indonesia stock exchange (IDX) in the year 2017. Descriptive analysis and a hierarchical multiple regression model are applied to analyse the data. No evidence has been found to suggest the role of corporate governance on CSR disclosure. However, results from the hierarchical regression analysis showed that foreign ownership moderates the relationship between the women on the board director and CSRD quality. The results of this study may provide some insight into how foreign ownership could play their role to ensure better corporate social disclosure. Companies should create more opportunities for foreigners to invest in their companies, in line with the current government’s expectations to increase the percentage of foreign ownership in Indonesian companies. Immediate action could also be taken by the government to revise the existing code of corporate governance, by considering higher percentage of women on the board of directors.